Introduction to and Discussion Summary of Wang Hui's Humanism as the Theme of Chinese Modernity - Hillis Miller, J. (Surfaces, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces Wang Hui's "Humanism as the Theme of Chinese Modernity" and reports on the central concerns that emerged in its discussion. It also includes the transcription of Wang Hui's preliminary remarks to the session.